After the Subject: Reading "Bartleby" with Sloterdijk. - Villiers, Dawid W. de (Philosophy & Literature, 2026)
This article essays the posthumanist charge of Herman Melville's short story "Bartleby, the Scrivener" by reading it alongside Peter Sloterdijk's essay "Rules for the Human Park." I propose that the latter's delineation of humanism—as an educative, domesticating project sustained by the cultural circulation of edifying letters assumed to tame the disinhibiting impulses of the animal rationale —enables us to consider "Bartleby" as invoking an unsettling, singular limit case that involves the collapse of the inhibiting/disinhibiting binary sustaining the subject of humanism. Within the framework of humanism, Bartleby emerges as aporia rather than problem.